SUSTENTABILIDADE NA FORMAÇÃO DE ADMINISTRADORES EM UNIVERSIDADES PÚBLICAS DO ESTADO DO PARANÁ IRATI - Kuzma, Edson Luis (2016)
Sustainability presents itself as a fundamental concept for balanced economic, social and environmental development, instigating and requiring transformations in various spheres of society. The aggravation of socio-environmental problems in recent times shows the need for and urgency of change in the world view, shared by companies, government and society. In this context, we have discussed ways of inserting sustainability in the lives of individuals and in the decisions of organizations, aiming to combine economic performance with conservation of the environment and social equity. Due to the functions they assume in the management of companies in their jobs, managers have the opportunity to include in their decisions and in the direction of productive organizations, attitudes and principles towards sustainability, triggering a change that starts within the business environment And reflects on society. The interest in approaching the sustainability theme of the training of administrators is gaining strength, especially in the last decade, arousing interest at different levels and, therefore, requiring transformations in educational institutions. Therefore, the present study was carried out with the objective of knowing the insertion of the sustainability theme in the Course of Graduation in Administration of the four Institutions of Higher Public Education of the State of Paraná, based on the theoretical models of the Creation of Sustainable Value of Hart And Milstein (2004) and the Sustainability Jargon of Sgarbi et al. (2008). In order to reach the proposed objective, a qualitative-quantitative or mixed-method approach was followed through multiple case studies with the following institutions: State University of Londrina, State University of Maringá, State University of Ponta Grossa and Federal University of Paraná. The analysis was developed through the appreciation of the disciplines offered in the courses, as well as from the perception of students and teachers about the insertion of the theme. The data treatment was performed through documentary analysis (menus and disciplines), univariate descriptive statistics and analysis of variance (perception of students and teachers), and interviews (teachers). The results indicate that there is no discipline offered in the study courses that deal specifically with the subject, even though several discuss related areas. The students' perception of the terms evaluated, as well as the teachers, generally leads to the understanding that some jargon is more often inserted in the training of administrators, while others do not receive representative attention. Each university, considering the differentiation between its disciplines and the direction given by the teachers, assumes particular behavior in relation to the others. The results of analysis of variance (ANOVA) also reveal that, in the case of the comparison between the universities, there were sufficiently significant differences between these, which are considerably larger than the variation between the different sustainability quadrants.